2009
DOI: 10.1007/s12601-009-0004-5
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic biomarker response of clam, Ruditapes decussates, to organophosphorous pesticides reldan and roundup: A laboratory study

Abstract: Clam Ruditapes decussates was used as a biomonitoring organism to measure the potential impact of pollution. The present study investigated histological alterations of R. decussates following a long-term exposure to a sublethal-level of pesticides Reldan and Roundup. The clams were taken to the laboratory and kept for days to adjust to a continuous closed flow system with quality water control. After the adjustment period, clams were exposed either to sublethal concentrations of Reldan (0.6 µl L − 1 ) or Round… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 21 publications
(17 reference statements)
2
5
0
Order By: Relevance
“…Histopathological alterations of gills of bivalve tissues have been shown to be responsive and sensitive to wide range of contaminants because they play an important role in respiration and food collection [33]- [35]. The histopathological changes of gills of bivalve in the present study are in agreement with [2] and [36] as they reported irregularity of gill lamellae of the cells, swelling of gill filaments and haemocytes infiltration of bivalve. Epithelial cells of the gills play a crucial role [37]; the damage in the epithelium results in serious dysfunction of tissues consequently leading to deleterious effect on the organization levels [2].…”
Section: Discussionsupporting
confidence: 88%
“…Histopathological alterations of gills of bivalve tissues have been shown to be responsive and sensitive to wide range of contaminants because they play an important role in respiration and food collection [33]- [35]. The histopathological changes of gills of bivalve in the present study are in agreement with [2] and [36] as they reported irregularity of gill lamellae of the cells, swelling of gill filaments and haemocytes infiltration of bivalve. Epithelial cells of the gills play a crucial role [37]; the damage in the epithelium results in serious dysfunction of tissues consequently leading to deleterious effect on the organization levels [2].…”
Section: Discussionsupporting
confidence: 88%
“…The histological details of DG and gills of C. aegyptiaca are very similar to earlier reports on different bivalve species (Agwuocha et al, 2011;El-Shenawy et al, 2009;Kumar et al, 2011). Moreover, the DG is the site of multiple oxidative reactions and may, therefore, be a site of substantial free radical generation.…”
Section: Discussionsupporting
confidence: 88%
“…Cilia covered the surface of each lamellae or filament and connective tissue was integrated into the base of the gill lamellae (Plate1; Fig 1). Gill tissue consists of two plates on each side of the body; each of these plates consists of a number of filaments lined by columnar epithelial cells with ovoid nuclei and the core of the plates consists of loose connective tissue (El-Shenawy et al, 2009).…”
Section: Resultsmentioning
confidence: 99%